How online discussion board activity affects stock trading: the case of GameStop - André Betzer; Jan Philipp Harries (Financial Markets and Portfolio Management, 2022)
In January 2021, the stock price of NASDAQ-listed GameStop Corporation surged more than twenty-fold for no discernible economic reason. Many observers attributed this broadly covered rise to retail investors, organizing themselves in Reddit's WallStreetBets community. While Social Media-organized trading is not a new phenomenon, the magnitude of the resulting swings in the share price and surge in trading volume of GameStop is unprecedented. Using financial data, as well as an extensive dataset of Reddit posts, we provide empirical evidence for the relationship of Reddit posts and GameStop (retail) trading. While we find a significant and positive relationship between Reddit posts and various trading measures in the following 30-min window in accordance with an attention-based mechanism, our results offer no indication for the informativeness of Reddit posts and hint at a complex and probably nonlinear interdependence between Social-media and trading activity, preventing proof of a one-directional, causal effect.
Keywords: D91; G14; G41; 330; GameStop; Retail trading; Trade volume; Market structure